Taking Continuing Education to a Land Down Under - Myatt, Angela E. (University of Texas Health Science Center San Antonio); Schardt, Connie; Kruesi, Lisa (University of Queensland) (2012)
Poster presented at 2012 Medical Library Association (MLA)